Studi Tentang Keterampilan Metakognisi, Berpikir Kritis dan Retensi dalam Pembelajaran Biologi Siswa SMAN 10 Kota Ternate - Ilham Majid (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the profile of students' metacognitive abilities, critical thinking and biological retention in learning biology. This study uses a descriptive method, with the population is class XI SMAN 10 Ternate City. The sample in this study is the total sample because the number of students is less than 100 students. Students are taught using the guided inquiry learning model, and STAD. The instrument used is a test of metacognitive skills and critical thinking skills in the form of an essay, consisting of 15 questions, with a reliability value of 0.760. Both tests were given at the beginning of learning (pretest) and at the end of learning (posttest). Research data, analyzed descriptively, based on the learning model used. The results showed that based on the learning model, the average post-test scores for metacognition and critical thinking skills and biological retention of students who were taught using the guided inquiry learning model were higher than the average post-test scores for metacognition and critical thinking. biological skills and retention of students who are taught using the STAD learning model